Spectrally pure far-UVC emission from AlGaN-based LEDs with dielectric band pass filters. (19th May 2022) - Guttmann, Martin; Lobo-Ploch, Neysha; Gundlach, Heiko; Mehnke, Frank; Sulmoni, Luca; Wernicke, Tim; Cho, Hyun Kyong; Hilbrich, Katrin; Külberg, Alexander; Friedler, Matthias; Filler, Thomas; Käpplinger, Indira; et al.
Abstract: AlGaN-based far ultraviolet-C (UVC) light emitting diodes (LEDs) with a peak emission wavelength below 240 nm typically show a long-wavelength tail at >240 nm that is detrimental to the use of the devices for skin-friendly antisepsis. We present the development of far-UVC LEDs with reduced long-wavelength emission using a HfO2 /SiO2 -based distributed Bragg reflector (DBR) filter. When the DBR filter is directly mounted on an LED package, the long-wavelength emission around 250 nm is reduced by two orders of magnitude while the transmitted output power is reduced down to 18%–27% of the initial value for DBR filters with cut-off wavelengths at 237–243 nm. As the transmission through the DBR filter depends strongly on the angle of incidence of the radiation, the transmitted output power of the spectrally pure far-UVC radiation can be doubled when an additional collimating lens is used on top of the LED package before passing through the filter.